A contribution to the investigation of high temperature corrosion resistance of aluminum coating steel - Kakaš, Damir (Journal of Production Engineering, 1984)
In this paper it was shown the problem which appear during the investigation of high temperature corrosion resistance of aluminum coating steel. Based on the experience which was got by the investigation of aluminum coated layer behavior with different composition of layer, it was given the proposal for improvement the methodology of high temperature corrosion resistance investigation.